Analisis Tes Objektif dan Uraian Pada Buku Teks Bahasa Indonesia Kelas VIII Menggunakan Taksonomi Bloom - Arin Anni Nabilah; Liana Rochmatul Wachidah; Aria Indah Susanti (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Test instruments are tools used to measure students' abilities, knowledge, or skills. Several types of test instruments include: objective, descriptive, and action tests. The purpose of this study was to analyze the level of cognitive domains of objective and descriptive tests in Indonesian language textbooks for grade VIII using Bloom's taxonomy. The focus of this study was objective tests and descriptive tests contained in Indonesian language textbooks for grade VIII junior high school in the poetry and speech chapters. This study used a qualitative literature study method using data sources in the form of books and scientific journal articles. literature study theory. The data source in this study was Indonesian language textbooks for grade VIII junior high school. Based on the results of the analysis of Indonesian language textbooks for grade VIII junior high school in the poetry and speech chapters reflecting the diversity of junior high school students' thinking levels according to Bloom's taxonomy, three objective test data were found, namely C2-Categorizing, C4-Analyzing, and C1-Identifying. Then eight data for descriptive text namely C2-Explaining and comparing, C4-Classifying, C3-Determining, C2-Categorizing, C3-Assigning, C2-Categorizing, C3-Determining, and C6-Creating. For that, the arrangement of objective and descriptive questions for junior high school students can be determined, namely using bloom's taxonomy (C2-C4), paying attention to language levels, variations in question forms, calibration with grids and KD/TP. Thus, in this study, the Indonesian language textbook for class VIII of junior high school is in accordance with Bloom’s taxsonomy and its curriculum.Instrumen tes merupakan alat yang digunakan untuk mengukur kemampuan, pengetahuan, atau keterampilan siswa. Tujuan penelitian ini yaitu untuk  menganalisis tingkat ranah kognitif jenis tes objektif dan uraian pada buku teks Bahasa Indonesia kelas VIII menggunakan taksonomi bloom. Fokus penelitian ini tes objektif dan tes uraian yang terdapat dalam buku teks Bahasa Indonesia kelas VIII SMP pada bab puisi dan pidato. Penelitian ini menggunakan metode kualitatif studi pustaka dengan menggunakan sumber data berupa buku-buku dan artikel-artikel jurnal ilmiah. Sumber data dalam penelitian ini adalah  buku teks Bahasa Indonesia kelas VIII. Berdasarkan hasil analisis buku teks Bahasa Indonesia kelas VIII SMP pada bab puisi dan pidato mencerminkan keberagaman tingkat berpikir siswa SMP sesuai dengan taksonomi bloom, ditemukan tiga data tes objektif yakni C2-Mengkategorikan, C4-Menganalisis, dan C1-Mengidentifikasi. Kemudian delapan data untuk teks uraian yakni C2-Menjelaskan dan membandingkan, C4-Mengklasifikasi, C3-Menentukan, C2-Mengkategorikan, C3-Menugaskan, C2-Mengkategorikan, C3-Menentukan, dan C6-Menciptakan. Untuk itu dapat ditentukan penyusunan soal objektif dan uraian untuk siswa SMP yaitu menggunakan taksonomi bloom (C2-C4), memperhatikan tingkat bahasa, variasi bentuk soal, kalibrasi dengan kisi-kisi dan KD/TP. Dengan demikian, pada penelitian ini buku teks bahasa Indonesia SMP kelas VIII sudah sesuai dengan taksnomi bloom dan kurikulum.